p-CuInS2/n-Polymer Semiconductor Heterojunction for Photoelectrochemical Hydrogen Evolution - Chae, Sang Youn; Lee, Myeongjae; Kim, Min Je; Cho, Jeong Ho; Kim, BongSoo; Joo, Oh-Shim (WILEY-V C H VERLAG GMBH, 2020)
An inorganic p-type CuInS2 semiconductor was combined with the semiconducting polymer of PNDI3OT-Se1 and PNDI3OT-Se2 with different HOMO/LUMO levels for photoelectrochemical hydrogen production. Charge transfer behaviors at polymer/CuInS2 junctions were investigated by electrochemical impedance spectroscopy. The heterojunction of p-CuInS2 and n-type polymer (both PNDI3OT-Se1 and Se2) successfully made p-n junctions and showed improved charge transfer. However, we found that higher HOMO levels of polymer than valence band maximum (VBM) of CuInS2 spurred charge recombination at interfaces. As a result, CuInS2/PNDI3OT-Se1/TiO2/Pt, which has suitable energy levels matched between PNDI3OT-Se1 and CuInS2, shows photocurrent (-15.67 mA cm(-2)) improved concretely when compared to a CuInS2/TiO2/Pt photoelectrode (-7.11 mA cm(-2)) at 0.0 V vs. RHE applied potential. Additionally, the photoelectrochemical stability of CuInS2/PNDI3OT-Se1/TiO2/Pt photoelectrode was also investigated.
Keywords: HIGH-PERFORMANCE; BAND-OFFSET; WATER; EFFICIENT; PHOTOCATHODES; DRIVEN; DEVICE; LAYERS; CELLS; BIVO4